Association of Blood Pressure at Successful Recanalization and Parenchymal Hemorrhage After Mechanical Thrombectomy With General Anesthesia - Cheng, Hui; Xu, Chao; Jin, Xing; Chen, Yigang; Zheng, Xu; Shi, Feina; He, Xudong; Hao, Yonggang; Jiang, Yun; Zhang, Jinhua; Chen, Zhicai (Frontiers in Neurology, 2020)
Background: To investigate the association between blood pressure (BP) at the time of recanalization and hemorrhagic transformation in large vessel occlusion (LVO) patients following mechanical thrombectomy (MT) with general anesthesia. Methods: We retrospectively reviewed our data base for patients with AIS who received MT between Jan 2018 and Dec 2019. The BP at two adjacent time points immediately after successful recanalization was recorded for subsequent calculation of mean BP (BPmean), maximum BP (BPmax), minimum BP (BPmin), range of BP (BPrange) and standard deviation of SP (BPSD). Hemorrhagic transformation was identified on 24-hour computerized tomography images according to European Cooperative Acute Stroke Study (ECASS) III trial. We use binary logistic regression analysis to investigate the association of BP parameters and the incidence of parenchymal hemorrhage (PH) and PH-2. Results: A total of 124 patients with anterior circulation LVO were finally included for analyses. After controlling for intravenous thrombolysis, procedure duration of mechanical thrombectomy, baseline NIHSS, baseline ASPECTS, and number of device passes, the results showed that every increment of 10 mmHg in SBPrange (OR 1.559; 95% CI 1.027 to 2.365; P=0.037) and SBPSD (OR 1.998; 95% CI 1.017 to 3.925; P=0.045) were independently associated with PH. After adjustment for intravenous thrombolysis, procedure duration of mechanical thrombectomy, baseline NIHSS, the results showed that every increment of 10 mmHg in SBPmean (OR 1.973; 95% CI 1.190 to 3.271; P =0.008), SBPmax (OR 1.838; 95% CI 1.199 to 2.815; P =0.005), SBPrange (OR 1.908; 95% CI 1.161 to 3.136; P =0.011) and SBPSD (OR 2.573; 95% CI 1.170 to 5.675; P =0.019) were independently associated with PH-2. Conclusion: Patients with higher systolic BP and variability at the time of successful recanalization were more likely to have PH-2 in LVO patients following MT with general anesthesia.